Correlation Knowledge to Hypothermic Handling Practices in Students - Dewi Sinta Windya Kustina (South East Asia Nursing Research, 2021)
Hypothermia is a decrease in core body temperature to <35˚C due to heat loss. Factors causing hypothermia are cold weather, exposure to cold winds at high altitudes, immersion in cold water, and prolonged exposure to cold. Hypothermia is more common in hikers or mapala because they do activities exploring the highlands. The purpose of this study was to determine the relationship between knowledge of hypothermia and the practice of handling hypothermia in Mapala. This study used a correlation study method with a cross-sectional approach. The population in this study were Mapala UNISSULA, UNNES, and USM with a total of 52 students. The sampling technique was purposive sampling, the number of samples of this study was 30 students. The results of the Spearman Rank statistical test obtained a value of ρ value of 0.738 (ρ ≥ 0.05), so it was stated that there was no relationship between knowledge of hypothermia and the practice of handling hypothermia in Nature Lovers Students. Recommendations from research so that mapala members increase their knowledge and practice in handling emergency hypothermia by conducting ongoing training.